A System Dynamics Model for Analyzing the Circular Economy Rebound - Cristina Beatrice Mallari; Richard Li; Jayne Lois San Juan (Chemical Engineering Transactions)
As the traditional linear economy becomes increasingly unsustainable, circular systems offer a compelling alternative, promoting the regeneration of materials and minimization of waste. Recently, however, the rebound effect has emerged as a critical constraint in the successful implementation of such strategies. The circular economy rebound occurs when efforts to enhance resource efficiency inadvertently stimulate higher levels of consumption or production. To address research gaps, this study proposes a system dynamics model to investigate the underlying drivers and dynamics of the rebound effect within circular economy systems. A hypothetical scenario was modeled, and the results support the premise that the circular economy rebound can exist under conditions of circularity. At the end of the simulation, a rebound equivalent to 2,443.73 kg-CO2 was observed, denoting that only 32.82 % of the potential environmental savings were realized. This highlights the critical need to re-evaluate the assumptions within circular economy frameworks. Sensitivity analysis was also conducted to explore the impact of fluctuations in key variables on the rebound dynamics. Overall, the study contributes to a deeper understanding of the complexities surrounding circular economies and provides valuable insights for stakeholders seeking to navigate the transition toward a more sustainable economic model.